PENGARUH DAYA TARIK IKLAN IPHONE DI MEDIA YOUTUBE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE : Survei Kepada Konsumen Iphone Fakultas Kedokteran Angkatan 2017 Universitas YARSI - Azizah Windiarti, - (2019)
This study discusses the influence of the attractiveness of Iphone ads on Youtube media on consumer decisions in the purchase of Iphone smartphones. The purpose of this study is to determine the magnitude of the influence of the attractiveness of Iphone ads on Youtube media on consumer decisions in Iphone smartphones. This study uses quantitative data with the type of survey method research. The data used is in the form of library and primary data. The theory in this study uses teeori S-O-R (Stimulus, Organism, Response). The sample in this study was 110 respondents with a simple random sampling technique that collected data using a questionnaire. Based on the results of the coefficient obtained the results of the influence of variable X (the appeal of advertising on the Youtube media) to Y (purchase decision). So it can be concluded that the attractiveness of Iphone ads on Youtube media influences the purchasing decisions of Iphone smartphone consumers at the YARSI University School of Medicine, which means that the greater the influence of the appeal of advertising on Youtube media is greater on consumer purchasing decisions